Math, asked by Anonymous, 1 year ago

❇️Question ⚠️

❎ NO SPAM ❎ ​

Attachments:

Answers

Answered by rahman786khalilu
1

hope it helps

mark as brainliest

Attachments:
Answered by sid590
1

y=(x²-1)(x-2)

this curve cuts x-axis at x=1,-1,2

now differentiate the curve,

dy/dx=2x(x-2)+(x²-1)=3x²-4x-1

substitute x values, we get

(dy/dx)(x=1)=-2

(dy/dx)(x=-1)=6

(dy/dx)(x=2)=3

equation for tangents are:

(y-0)=(-2)(x-1) => 2x+y-2=0

(y-0)=(6)(x+1) => 6x-y+6=0

(y-0)=(3)(x-2) => 3x-y-6=0

hope this helps you out

Similar questions